Oral microbiome diversity among Cheyenne and Arapaho individuals from Oklahoma. Issue 2 (30th June 2016) - Ozga, Andrew T.; Sankaranarayanan, Krithivasan; Tito, Raúl Y.; Obregon‐Tito, Alexandra J.; Foster, Morris W.; Tallbull, Gloria; Spicer, Paul; Warinner, Christina G.; Lewis, Cecil M.
Abstract: Objectives: There is a major ascertainment bias in microbiome research, with individuals of predominately European ancestry living within metropolitan areas dominating most studies. Here we present a study of the salivary microbiome within a North American Indian community. This research is the culmination of four years of collaboration and community engagement with Cheyenne & Arapaho (C&A) tribal members from western Oklahoma. Materials and Methods: Using 16S rRNA gene amplification and next‐generation sequencing, we generated microbial taxonomic inventories for 37 individuals representing five towns within the C&A tribes. For comparison, we performed the same laboratory techniques on saliva samples from 20 non‐native individuals (NNI) from Norman, Oklahoma. Results: The C&A participants differ from the NNI in having reduced within‐individual species richness and higher between‐individual variation. Unsupervised clustering analyses reveal that three ecological groupings best fit the data, and while C&A individuals include assignments to all three groups, the NNI individuals are assigned to only one group. One of the ecological groups found exclusively among C&A participants was characterized by high abundance of the oral bacterial genus Prevotella . Discussion: The C&A and NNI participants from Oklahoma have notable differences in their microbiome diversity, with a wider range of variation observed among the C&A individuals, including a higher frequency of bacteria implicated in systemic disorders. Overall, this study highlights the importance of engagement with indigenous communities, and the need for an improved understanding of human microbiome diversity among underrepresented groups and those individuals living outside of metropolitan areas.